1996
DOI: 10.1179/sic.1996.41.4.193
|View full text |Cite
|
Sign up to set email alerts
|

A black paint on the facade of a Renaissance building in Bergamo, Italy

Abstract: The first storey of the Casa dell'Arciprete in Bergamo, Italy, built of grey limestone, is today covered with a black paint layer. A detailed investigation of the morphology and composition of this layer was necessary in order to plan conservation work in 1993. Optical and scanning electron microscopy showed that the layer is very thin and closely follows the surface of the stone. Energy-dispersive X-ray (EDX) spectra of polished cross-sections did not reveal significant differences between the elemental compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…[46,51,52]. Their co-presence, often found on monument surfaces [53] long exposed to atmospheric pollutants, contributes to the formation of the characteristic 'patina' . Here the term "patina" indicates, without discrimination, all the sequential layers, of both biotic and abiotic origin, possibly deposited over the "noble patina", formed over the underlying carbonate stone and eventually protective against the progressive erosion due to acidic rain and aggressive atmospheric components [54,55].…”
Section: The Widementioning
confidence: 99%
“…[46,51,52]. Their co-presence, often found on monument surfaces [53] long exposed to atmospheric pollutants, contributes to the formation of the characteristic 'patina' . Here the term "patina" indicates, without discrimination, all the sequential layers, of both biotic and abiotic origin, possibly deposited over the "noble patina", formed over the underlying carbonate stone and eventually protective against the progressive erosion due to acidic rain and aggressive atmospheric components [54,55].…”
Section: The Widementioning
confidence: 99%
“…The observation of the interface between calcite substratum and the above mentioned secondary minerals is an important step in the explanation of alteration process of artifacts of historic and artistic interest 37 . Studies of the black paint has shown the presence of oxalates in the paint with serious implications for remediation 38 .…”
Section: Introductionmentioning
confidence: 99%
“…As revealed by the number of peaks composing the carbon 1s signal, listed in Table 2, the blank surface of marbles is covered by carbonaceous contaminants, mainly consisting of aliphatic chains containing oxygen groups and some nitrogen and sulfur groups. Additional unspeci ed adsorbed compounds are grouped, in Table 2 assignments, as C organic belonging to the lower zone of Binding Energy typical of carbides, graphite, polycyclic and aromatic carbons [39,43,44]. Their co-presence, often found on monumental surfaces [45] long in uenced by atmospheric pollutants, contributes to the formation of the characteristic 'patina'.…”
Section: Xps Analysis Of Marble Surfacesmentioning
confidence: 99%